Comparative benefits of orange heirloom tomatoes over red tomatoes for bone health : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Nutritional Science at Massey University, Manawatū, New Zealand - Walallawita Kankanamge, Umani Shanika Walallawita (Massey University, 2022)
Bone loss, common in women after menopause, is characterized by reduced bone mineral density with disruption of bone microarchitecture, leading to higher fracture risk and osteoporosis. There are few treatments, and most have adverse side effects. Intervention studies have shown protective effects of lycopene against bone loss in animal models. Lycopene is a lipid-soluble carotenoid found mainly in tomatoes. The molecule exists in all-trans- and a variety of cis- configurations; and cis- lycopene isomers have been reported to be more bioavailable than all-trans-. ‘Moonglow’, an orange heirloom tomato, contains >90% of its lycopene in cis- isomeric form and thus may be a better source of naturally bioavailable lycopene than red tomato, which contains all-trans- lycopene. We hypothesised that consumption of moderate daily doses of whole ‘Moonglow’ tomato would reduce bone loss more effectively than red tomato in rat and cell models of osteoporosis. In vivo, ‘Moonglow’ tomato supplementation delivered physiologically relevant plasma lycopene concentrations within four days of feeding. The post-ovariectomy rat model was successful in accelerating bone loss. ‘Moonglow’ tomatoes delivered a higher plasma lycopene concentration than red tomatoes and were beneficial in reducing a bone turnover marker compared to red tomatoes, even when fed after initiation of bone loss, but did not improve bone mineral density. Ovariectomy reduced gut bacteria abundance; compared to red, ‘Moonglow’ tomato feeding restored the numbers of Lactobacillus, Enterococcus, Bacteroides and E. coli. In vitro cell culture studies showed that both red and ‘Moonglow’ tomato hexane extracts induced a significant decrease in the number of bone-resorbing TRAP-positive osteoclasts at 10 µmol/L lycopene concentration. In conclusion, there were slight differences in bone measurements between red or 'Moonglow' tomato feeding, except for the significant reduction of one bone turnover marker. This suggests that a higher dose and longer intervention period may be needed to provide clinically important improvement against bone loss. However, significantly higher plasma lycopene followed ‘Moonglow’ feeding compared to red tomatoes, indicating its better bioavailability and demonstrating value for future research on health benefits from ‘Moonglow’ tomatoes. In addition, findings from this study provide support for the importance of exploring the potential prebiotic-like effect of tomatoes and the mechanisms associated with changes in gut bacteria.
Keywords: Osteoporosis; Alternative treatment; Lycopene; Tomatoes; Color; 321004 Nutritional science